2009
DOI: 10.1111/j.1502-3885.2009.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of glaciohydraulic supercooling in the formation of stratified facies basal ice: Svínafellsjökull and Skaftafellsjökull, southeast Iceland

Abstract: There is need for a quantitative assessment of the importance of glaciohydraulic supercooling for basal ice formation and glacial sediment transfer. We assess the contribution of supercooling to stratified facies basal ice formation at Svı´nafellsj¨okull and Skaftafellsj¨okull, southeast Iceland, both of which experience supercooling. Five stratified basal ice subfacies have previously been identified at Svı´nafellsj¨okull, but their precise origins have not been determined. Analysis of stratified basal ice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(97 citation statements)
references
References 41 publications
4
90
1
2
Order By: Relevance
“…Numerous ice facies with differing physical characteristics have been described from the base of glaciers and ice sheets [see Hubbard et al, 2009]. Of these, debris-rich ice facies are typically thought to have formed due to the entrainment of subglacial material via four main processes: (1) en masse freeze-on [e.g., Weertman, 1961], (2) regelation around bedrock obstacles [e.g., Kamb and LaChapelle, 1964], (3) regelation into the bed [e.g., Iverson, 2000], and (4) glacihydraulic supercooling [e.g., Cook et al, 2010]. Existing work on basal ice sequences at surge-type glaciers has highlighted the importance of tectonic deformation in their formation, typically resulting in the thickening of units through faulting and folding [Sharp et al, 1994;Larsen et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous ice facies with differing physical characteristics have been described from the base of glaciers and ice sheets [see Hubbard et al, 2009]. Of these, debris-rich ice facies are typically thought to have formed due to the entrainment of subglacial material via four main processes: (1) en masse freeze-on [e.g., Weertman, 1961], (2) regelation around bedrock obstacles [e.g., Kamb and LaChapelle, 1964], (3) regelation into the bed [e.g., Iverson, 2000], and (4) glacihydraulic supercooling [e.g., Cook et al, 2010]. Existing work on basal ice sequences at surge-type glaciers has highlighted the importance of tectonic deformation in their formation, typically resulting in the thickening of units through faulting and folding [Sharp et al, 1994;Larsen et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The dispersed facies data do not produce a freezing slope on a coisotopic plot; the absence of a freezing slope indicates that the dispersed facies is not formed by bulk adfreezing of water from a single initial source of limited extent with a specific isotopic composition [Souchez et al, 1988]. This suggests that grain boundary melting and refreezing is not confined to one cycle (e.g., bulk adfreezing) sourced only from the englacial facies but may be the result of multiple melting and partial refreezing events with numerous water sources in an open system [Sharp et al, 1994;Cook et al, 2010]. This process is envisaged as partial melting of ice crystals, followed by redistribution of water via flow along intercrystalline veins and eventually partial refreezing and recrystallization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The more restricted pseudostratified outcrops are potentially the rare products of melt-out from supercooled glacier ice, a notable feature of the Icelandic south coast glacier lobes (Cook et al, 2010;Cook, Graham, Swift, Midgeley, & Adam, 2011;Cook, Knight, Richard, Robinson, & Adam, 2007;Cook, Swift, Graham, & Midgley, 2011;Roberts et al, 2002), but predominantly the diamictons display features that are diagnostic of a subglacial traction till genesis such as fissility, compaction and reasonably strong clast macrofabrics (Evans, 2000(Evans, , 2017Evans et al, submitted;Evans, Phillips, Hiemstra, & Auton, 2006;Jónsson et al, 2016).…”
Section: Till and Moraines And Associated Featuresmentioning
confidence: 99%
“…Such entrainment, elevation, and transport is likely to be most effective under warm-based conditions, which facilitate the development of debris-rich basal ice sequences (Sharp et al, 1994;Knight, 1997), debris-rich shear planes (Glasser et al, 1998), and injections of debris into basal crevasses (Rea and Evans, 2011). It is suggested that the entrainment of subglacial debris is particularly efficient on the adverse slopes of overdeepenings, where supercooling processes result in the formation of debris-rich basal ice (Cook et al, 2010) and debris is entrained and elevated via shear planes (Swift et al, 2002). As a consequence, some of the largest moraines may well form in front of temperate glaciers with terminal overdeepenings (see Swift et al, 2002;Cook and Swift, 2012).…”
Section: Supply Of Debris To Glacier Marginsmentioning
confidence: 99%